Statistical Analysis of Leadership Styles and Their Impact on Hierarchical Effectiveness in Organizations (Global Journal of Sciences, 2025)
This research investigates the optimistic role of leadership styles in enhancing employees' hierarchical effectiveness within organizations, analyzed through statistical methodologies. Leadership is a critical factor influencing both the achievement and frustration of employees while managing organizational dynamics. A survey-based approach was employed, collecting data from 350 employees (210 males and 140 females) via questionnaires. Statistical tools, including regression analysis and correlation studies, were used to examine the relationships between leadership styles and hierarchical effectiveness. The findings indicate that charismatic, bureaucratic, and transactional leadership styles are negatively associated with hierarchical effectiveness, while transformational, autocratic, and democratic approaches show a positive correlation. Leaders who adopt optimistic and supportive styles not only improve hierarchical dynamics but also foster an innovative, satisfying, and sustainable organizational environment. This study underscores the importance of applying statistical techniques to evaluate and optimize leadership strategies for enhanced organizational performance.
Keywords: Organizational performance; Statistical analysis; Transformational; Bureaucratic; Charismatic; Democratic; Leader-ship Approaches